Character/Text Data Compression and Encryption by Compressive Sensing and Hybrid Cryptography - Atar, Ertan; Ersoy, Okan K.; Ozyilmaz, Lale (IEEE, 2016)
Compressed sensing (CS) is a methodology allowing linear measurements much fewer in number than the length of the original signal vectors. This is made possible by using a measurement matrix which converts the original signal to a much shorter signal. For CS to work, it is necessary that the original signal is sufficiently sparse so that it can be reconstructed from the compressed signal. Hybrid cryptography combines symmetric and asymmetric cryptographies. In order to increase security, the symmetric keys used are transmitted to the receiver by asymmetric cryptography. In this study, the proposed character/text input is proposed to be sensed by compressive sensing using the method of orthogonal matching pursuit (OMP), and then to be encrypted by hybrid cryptography using a transform and amplitude-phase keys similarly to a 4f system of optical cryptography. The overall system achieves both data compression and encryption.
Keywords: Compressive sensing; orthogonal matching; pursuit algorithm; hybrid cryptography; discrete cosine-III; transform; complex phase key; data size reduction; Engineering